The impact of far-UVC radiation (200-230 nm) on pathogens, cells, skin, and eyes - a collection and analysis of a hundred years of data - Hessling, Martin; Haag, Robin; Sieber, Nicole; Vatter, Petra (German Medical Science GMS Publishing House, 2021)
Background: The ongoing coronavirus pandemic requires new disinfection approaches, especially for airborne viruses. The 254 nm emission of low-pressure vacuum lamps is known for its antimicrobial effect, but unfortunately, this radiation is also harmful to human cells. Some researchers published reports that short-wavelength ultraviolet light in the spectral region of 200-230 nm (far-UVC) should inactivate pathogens without harming human cells, which might be very helpful in many applications.Methods: A literature search on the impact of far-UVC radiation on pathogens, cells, skin and eyes was performed and median log-reduction doses for different pathogens and wavelengths were calculated. Observed damage to cells, skin and eyes was collected and presented in standardized form.Results: More than 100 papers on far-UVC disinfection, published within the last 100 years, were found. Far-UVC radiation, especially the 222 nm emission of KrCl excimer lamps, exhibits strong antimicrobial properties. The average necessary log-reduction doses are 1.3 times higher than with 254 nm irradiation. A dose of 100 mJ/cm reduces all pathogens by several orders of magnitude without harming human cells, if optical filters block emissions above 230 nm.Conclusion: The approach is very promising, especially for temporary applications, but the data is still sparse. Investigations with high far-UVC doses over a longer period of time have not yet been carried out, and there is no positive study on the impact of this radiation on human eyes. Additionally, far-UVC sources are unavailable in larger quantities. Therefore, this is not a short-term solution for the current pandemic, but may be suitable for future technological approaches for decontamination in rooms in the presence of people or for antisepsis.